PENJERNIHAN AIR SUMUR UNTUK KEBUTUHAN SEHARI-HARI DI DAERAH KAMPUNG BYOBYOSI DISTRIK ARSO KABUPATEN KEEROM - Bodian Davin Panggabean; Lia Medy Tandy (JURNAL PENGABDIAN PAPUA, 2019)
Dedication is directly applied in the field with the management of using equipment that is cheap, simple, and affordable and can be directly benefited by the community of sarmi village. To overcome high water turbidity levels required a processing with the aim of reducing and even removing the level of turbidity and odor of the water. One of the treatment is filtration method using fibers, charcoal, sand, foam, and gravel as filter and absorbent material, as well as paralon pipes as medium where the processing place. The result of this water treatment is not prioritized for the purposes of drinking water, but for the purposes of bathing and washing. With the precense of groundwater processing, so in this case a little more the need for clean water for the community can be resolved, where the color and odor in the groundwater can be  neutralized to odorless and colorless, so the water is feasible to be used for everyday purposes in particular bathing and washing. Keywords: Physical properties of groundwater, treacment.